2022
DOI: 10.1186/s12966-022-01305-0
|View full text |Cite
|
Sign up to set email alerts
|

“All the fun stuff, the teachers say, ‘that’s dangerous!’” Hearing from children on safety and risk in active play in schools: a systematic review

Abstract: Background Active play is vital for healthy child development, and schools are a valuable setting to promote this behaviour. Understanding the determinants of children’s physical activity behaviour during recess, particularly the role of risk-taking and the influence safety concerns have on active play, is required. This systematic review aimed to 1) synthesise qualitative research with children that explored their perceptions of safety and risk in active play during recess in elementary and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…The number of studies meeting the eligibility criteria at the end of stage 3 (n = 46), and the depth of data produced, led to a further stage of screening to narrow the scope of the review. For the final, Stage 4 screening, the study population was narrowed to adults, with research conducted with children subjected to a separate review [56].…”
Section: Study Screening and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies meeting the eligibility criteria at the end of stage 3 (n = 46), and the depth of data produced, led to a further stage of screening to narrow the scope of the review. For the final, Stage 4 screening, the study population was narrowed to adults, with research conducted with children subjected to a separate review [56].…”
Section: Study Screening and Selectionmentioning
confidence: 99%
“…Research examining children's perspectives on recess [55] and safety and risk in active play in schools [56] has been subjected to systematic review, however, to our knowledge, there has been less attention to adults' perspectives and experiences. A previous review examined barriers and facilitators to adventurous play in schools, however, its scope was narrow with respect to play (focussing on "exciting, thrilling play where children are able to take age-appropriate risks" in contrast to active play more broadly, as defined by Truelove and colleagues and described above), and most included studies (six of nine) were evaluations of adventurous play interventions, which may have limited relevance outside of an intervention context ( [57], p.21).…”
Section: Introductionmentioning
confidence: 99%
“…This requires a better understanding of what children with and without disabilities seek in playgrounds. No other review has been found [13,14,21,23,[37][38][39][40][41] that investigated published peer-reviewed literature that considered perspectives of children with and without disabilities and their play experiences in playgrounds. This scoping review aims to summarize the users' (children with and without disabilities) play experiences and gain insight into what environmental qualities maximize the play experience in community playgrounds for all children.…”
Section: Introductionmentioning
confidence: 99%
“…The value of play was raised firmly into public awareness during the Covid‐19 pandemic as children's opportunities to play was reduced due to school and park closures (Jerebine et al, 2022; Szpunar et al, 2022). Despite this, play in early adolescence remains under‐researched—in a recent systematic qualitative review of outdoor play at school, all 41 research studies included in the final analysis were conducted with children in Year 7 or below (Jerebine et al, 2022), and none focussed on high school.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Shoari et al (2021) found that more ‘than 60% of children and adolescents in London do not have adequate open and green space at their school’ (p. 379). Studies have focussed on increasing fitness and decreasing obesity, and many do not consider other aspects of play such as a forum to connect and be with friends (Jerebine et al, 2022; Massey et al, 2020; Mroz & Woolner, 2020).…”
Section: Introductionmentioning
confidence: 99%